Eosinophilia-associated muscle disorders: an immunohistological study with tissue localisation of major basic protein in distinct clinicopathological forms. Issue 5 (12th January 2009) - Cantarini, L; Volpi, N; Carbotti, P; Greco, G; Aglianò, M; Bellisai, F; Giannini, F; Alessandrini, C; Grasso, G; Galeazzi, M
Abstract : Aims: ( a ) To evaluate tissue eosinophil density, location of eosinophil cytotoxic products, histopathological muscle changes and inflammatory cell types in different eosinophilia-associated myopathies that are clinicopathologically heterogeneous. ( b ) To determine the immunohistological range of tissue eosinophil density in non-eosinophilic inflammatory myopathies. Methods: Muscle biopsy specimens from seven patients with blood and/or tissue eosinophilia and clinicolaboratory myopathic signs (five chronic course myopathies, one subacute onset fasciitis/myositis, one acute myositis), and from 18 non-eosinophilic inflammatory myopathies, underwent routine staining, inflammatory infiltrate immunophenotyping, immunostaining for eosinophil major basic protein (MBP) and transmission electron microscopy examination. Eosinophil and total inflammatory cell counts were statistically analysed. Results: Histological examination showed occasional or no infiltrating eosinophils in all cases. MBP staining showed that tissue eosinophil density and percentages in eosinophilia-associated myopathies were significantly higher than in idiopathic myositides. Extracellular MBP diffusion, the hallmark of eosinophil cytotoxicity, was recurrent on sarcolemma and endothelium. Electron microscopy showed eosinophils close to sarcolemma, abundant mast cells, and capillary endothelial swelling. Immunostaining detected a higher mean eosinophil density in idiopathic myositides than previously assessed histologically. Conclusions: MBP immunohistology on skeletal muscle, previously performed only for acute eosinophilic polymyositis, suggests that eosinophil-mediated injury of muscle cells may occur in a wider spectrum of less aggressive eosinophilia-associated myopathies than previously thought. As conventional histology is likely to underestimate this leucocyte subset, MBP staining may be a useful tool in the analysis of tissue infiltration of eosinophils as a possible treatment target.